New subgenera of Ellipteroides Becker (Tipuloidea: Limoniidae) and their phylogenetic implications - Iwona Kania-Kłosok; Daubian Santos; Katarzyna Kopeć; Wiesław Krzemiński (Scientific Reports)
Abstract A new subgenus of Ellipteroides—Jantares subgen. nov.—is reported from Eocene Baltic amber with one new species Ellipteroides (Jantares) hansi sp. nov. This new subgenus is easily distinguishable from the other subgenera by a male terminalia with interbases very long, a simplified gonostylus, wing venation by the combination of a closed discal cell and m-cu placed at Mb. After numerous comparisons of the morphological characteristics of subgenera of the genus Ellipteroides, we defined this species in a new subgenus. The newly described species herein is the second evidence on the occurrence of Ellipteroides in the fossil record. The new discovery adds to the knowledge of the crane flies’ history evolution, especially its Eocene stage and new view on phylogeny within the genus Ellipteroides. A phylogenetic analysis was carried out and we propose a new classification within the genus Ellipteroides. This system adds a new subgenera E. (Afroellipteroides) subgen. nov., E. (Iberiopteroides) subgen. nov., E. (Photogonomyia) subgen. nov., and new combinations intendent to correct morphological inconsistencies in the current taxonomy of the group. The results of the analysis are important for understanding phylogenetic relationships within the genus, but also for determining the model of various stages of evolution of Limoniidae using the fossil records of the family.